The Treatment of Distal Clavicle Fractures With Coracoclavicular Ligament Disruption: A Report of 10 Cases - (:unkn) unknown (My University, 2005)
Fractures of the distal third of the clavicle with coracoclavicular ligament disruption have been associated with delayed union or nonunion. A combined surgical technique for the fracture fixation and ligament repair for acute fractures was developed. The technique includes K-wire fixation and suture anchor placement with Ethibond suture to the coracoid process. The results of this combined technique were evaluated. Prospective, consecutive case series. Surgical treatment was performed at the Department of Orthopedics and Traumatology. Ten patients with acute fractures of the distal third of the clavicle were enrolled with a mean follow-up period of 24.1 (range, 12-36) months. A single suture anchor was placed on the coracoid process in a vertical position. The Ethibond suture attached to the anchor was used to depress the elevated proximal part of the clavicle by pulling it down to the coracoid process where the anchor was placed. The suture was pulled over the proximal clavicle and tied. The distal fragment was fixed to the proximal clavicle by an intramedullary K-wire. The torn coracoclavicular ligaments were approximated using absorbable suture. The patients were evaluated by the Constant scores and Modified Shoulder Rating Scale. The mean Constant score was 96.6 points in the last follow-up. Nine patients had excellent results, and 1 patient had a good result, using the Modified Shoulder Rating Scale. This is a reliable technique with encouraging results for treating displaced distal third clavicle fractures with coracoclavicular ligament disruption. © 2005 Lippincott Williams & Wilkins, Inc.
Keywords: Coracoclavicular ligament restraint loss; Distal third clavicle fracture; Neer type IIb fractures